Knowledge on physical activity participation among secondary school students in Kakamega County, Kenya: descriptive study on 422 students aged 14–18 years - Joseph Muchiri Ndunda; Edwin Wamukoya; Roselyne Odiango (BMJ Open Sport & Exercise Medicine)
Introduction Physical activity is important for personal growth and development among students. About two million deaths are reported yearly, arising from inactivity. 81% of students do not meet the recommendations; hence they are exposed to unhealthy behaviour.Objective To determine the knowledge of secondary school students on physical activity in Kakamega County.Methods A descriptive survey design was used with a questionnaire developed with two sections; on knowledge and physical activity participation. A sample size of 422 students aged 14–18 years was used. Self-reporting questionnaires were administered. The data were collected within a week and analysed through descriptive and comparative statistical analyses. We used Pearson correlation to test the relationship between knowledge and physical activity participation, and independent t-test to check gender differences in physical activity and knowledge. Findings were considered significant at p<0.05.Results Male students were 194 (47.1%) while 218 (52.9%) were female students, with the majority being 17 years of age with a mean of 16 and SD of 1.4. Kakamega High School (31.0%) formed the majority of the students. There was a positive and significant relationship (r=0.159, p<0.001) between knowledge and physical activity. There were no significant differences (t (438)=−0.738, p=0.434) in the scores of males (M=2.07, SD=0.690) and females (M=2.13, SD=0.738). With a mean difference of=−0.054, 95% CI: −0.188 to 0.081). From the findings, 59.4% of students had adequate knowledge of physical activity.Conclusions The study highlights the need for more emphasis on educating students about the negative and positive health impacts of inactivity and actively engaging in physical activity both at school and at home. This will improve knowledge levels.